3
$\begingroup$

Consider the equation $$ X_1^3+X_2^3+X_3^3 = Y_1^3+Y_2^3+Y_3^3. \tag{$\star$} $$

Does this have a complete solution (a.k.a. parameterization) in integers? If not, does it have a complete solution in rational numbers?

I know the [integral and/or rational] solutions to other related equations — such as the 3.2.2 equation $$ X_1^3+X_2^3 = Y_1^3+Y_2^3 $$ and the 3.1.3 equation $$ X_1^3 = Y_1^3+Y_2^3+Y_3^3. $$ (see, for example, Choudhry’s paper) — but I have yet to find any paper giving the complete rational or integral solution to ($\star$).

$\endgroup$
4
  • $\begingroup$ @StevenGregory: That's a solution to the 3.1.3 equation. How does it answer my question? $\endgroup$ Commented Sep 20, 2016 at 2:05
  • $\begingroup$ artofproblemsolving.com/community/c3046h1046691__2 $\endgroup$
    – individ
    Commented Sep 20, 2016 at 10:52
  • $\begingroup$ @individ: Nice identities! I would love to see a proof that they represent the complete rational and/or integral solution(s). $\endgroup$ Commented Sep 20, 2016 at 12:30
  • $\begingroup$ See also this post on $3$rd and other powers. $\endgroup$ Commented Sep 22, 2016 at 2:41

1 Answer 1

3
$\begingroup$

Update:

Yes, there is a complete rational solution. Since we are dealing with a homogeneous equation, it is best to consider rational points on,

$$x_1^2+x_2^2 =1\tag1$$

$$x_1^3+x_2^3+x_3^3 =1\tag2$$

$$x_1^3+x_2^3+x_3^3+x_4^3+x_5^3 =1\tag3$$

to reduce the number of variables. The complete rational solution to $(1)$ and $(2)$ are well-known. It turns out the complete rational solution for $(3)$ is,

$$\color{blue}{\big(a + (a + b)\gamma\big)^3 + (a \gamma - b)^3 + \big(c + (c + d)\gamma\big)^3 + (c \gamma - d)^3 + \gamma^3 = 1}\tag4$$

where,

$$\gamma=\frac{-a^3 + b^3 - c^3 + d^3 + 1}{a^3 + (a+b)^3+c^3+(c+d)^3+1}\tag5$$

and can be found by generalizing the approach used by Choudhry in the paper cited by the OP.

Proof:

Equating the five terms of $(3)$ and $(4)$, one can easily solve for the five unknowns $a,b,c,d,\gamma$ as,

$$a = \frac{x_1+x_2x_5}{\beta},\quad b = \frac{-x_2+(x_1-x_2)x_5}{\beta}$$ $$c = \frac{x_3+x_4x_5}{\beta},\quad d = \frac{-x_4+(x_3-x_4)x_5}{\beta}$$ $$\gamma = x_5, \quad\quad\beta = x_5^2+x_5+1$$

Substituting these into $(5)$, the equality holds only if the $x_i$ satisfies $x_1^3+x_2^3+x_3^3+x_4^3+x_5^3 =1$, thus proving the assertion.

Example:

The smallest solution to $(3)$ is,

$$\big(\tfrac{1}{4})^3+\big(\tfrac{1}{4})^3+\big(\tfrac{2}{4})^3+\big(\tfrac{3}{4})^3+\big(\tfrac{3}{4})^3=1\tag6$$

Equating terms with $(4)$ one finds $a,b,c,d,\gamma$ as,

$$a=\tfrac{7}{37},\;b=\tfrac{-4}{37},\;c=\tfrac{17}{37},\;d=\tfrac{-15}{37},\;\gamma=\tfrac{3}{4}$$

If there is a zero term,

$$0+\big(\tfrac{1}{7})^3+\big(\tfrac{1}{7})^3+\big(\tfrac{5}{7})^3+\big(\tfrac{6}{7})^3=1\tag7$$

then,

$$a=\tfrac{6}{127},\;b=\tfrac{-13}{127},\;c=\tfrac{37}{127},\;d=\tfrac{-59}{127},\;\gamma=\tfrac{6}{7}$$

and so on.

$\endgroup$
8
  • $\begingroup$ What's the approach for such a case? $$x^3+y^3+z^3=a^3+b^3$$ $\endgroup$
    – individ
    Commented Sep 21, 2016 at 17:36
  • $\begingroup$ @individ: The same general identity covers it, but $a,b,c,d,e$ has to be chosen so one of the $x_i$ vanishes. $\endgroup$ Commented Sep 22, 2016 at 7:14
  • $\begingroup$ You, sir, are my hero. =) $\endgroup$ Commented Sep 22, 2016 at 10:49
  • $\begingroup$ @KierenMacMillan: Pleasure to be of service. =) $\endgroup$ Commented Sep 22, 2016 at 12:00
  • 1
    $\begingroup$ @KierenMacMillan I believe it does. You can scale $(4)$ so the last addend is $e^3$, not $1$, if you want $5+1$ variables (like Choudhry's $3+1$). And corresponding changes to $(3)$ also. $\endgroup$ Commented Sep 23, 2016 at 3:05

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .